Pengembangan Aplikasi E-Commerce pada PT Solusi Informasi Berbasis Web - Tazakka Ria Ramadhan (UNIVERSITAS KALBIS, 2022)
This study has the aim of developing an e-commerce application that is used by PT Panah Solusi Information to conduct buying and selling goods that occur at the company PT Panah Solusi Information. The method used to develop a website-based software application in this research is the Rational Unified Process (RUP) and uses Entity Relationship Diagram (ERD) modeling, Windows Navigation Diagrams, and Unified Modeling Language (UML) which includes Use-Case Diagrams, and Activity Diagrams. This website-based application is built using the Hyper Text Markup Language (HTML), Cascading Style Sheet (CSS), Hypertext Preprocessor (PHP), JavaScript, and MySQL programming languages which are used as application databases, based on the User Acceptance Test (UAT) this application can assist transactions that occur at PT Arrow solutions Information. The result of this research is the e-commerce application of PT Panah Solusi Informasi.